1995
DOI: 10.1088/0953-4075/28/2/016
|View full text |Cite
|
Sign up to set email alerts
|

The positron-hydrogen system at low energies

Abstract: Calculations of lowenergy positron-hydrogen and positroniumproton scattering using the close coupling method are reported at eErgkk belowthe ionization threshold. The chanAelspace ir&uded six hydrogen (Is. 2s. 2p, 3s. 3p and 3d) and six positronium (Is, 2s. 2p, 3s. 4s and 3p) states. Comparisons with more accurate calculations demonstrate that this model should give integrated cross sections accurate to 10%. Cross sections are computed with a fine energy mesh and a total of 11 resonances associated with the H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
68
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 47 publications
(12 reference statements)
7
68
3
Order By: Relevance
“…We also compare the present phase shifts with those obtained by Schwartz (1961) [14] obtained by using the Kohn variational principle, Houston and Drachman (1971) [18], by using the Harris method, Kohn variational calculation of Humberston and Wallace (1972) [19], and Gien (1997) [20], by using the Harris-Nesbet method in Table 2. The 21-state close-coupling approximation phase shifts obtained by Mitroy and Ratnavelu (1995) [21][22][23] are lower than the present results. [21][22][23] has reported a large basis close-coupling calculation of scattering at low energies.…”
Section: Introductioncontrasting
confidence: 84%
See 1 more Smart Citation
“…We also compare the present phase shifts with those obtained by Schwartz (1961) [14] obtained by using the Kohn variational principle, Houston and Drachman (1971) [18], by using the Harris method, Kohn variational calculation of Humberston and Wallace (1972) [19], and Gien (1997) [20], by using the Harris-Nesbet method in Table 2. The 21-state close-coupling approximation phase shifts obtained by Mitroy and Ratnavelu (1995) [21][22][23] are lower than the present results. [21][22][23] has reported a large basis close-coupling calculation of scattering at low energies.…”
Section: Introductioncontrasting
confidence: 84%
“…The 21-state close-coupling approximation phase shifts obtained by Mitroy and Ratnavelu (1995) [21][22][23] are lower than the present results. [21][22][23] has reported a large basis close-coupling calculation of scattering at low energies. The phase shifts of these calculations are lower than the present results given in Table 2.…”
Section: Introductioncontrasting
confidence: 84%
“…One of the most promising methods that has been suggested for producing antihydrogen [5 -7] is to use the charge-exchange process computing the integral cross section from the positronium ground state, differential cross sections were also computed [11]so that the recoil conditions appropriate to the collision could also be determined. Another very recent calculation was the hyperspherical close-coupling calculation of Igarashi, Toshima, and Shirai [12].The cross sections from this model are expected to be of similar accuracy to those of Mitroy and Ratnavelu [11]for the ground state.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the charge-transfer cross section should peak around 14~ao for incident positronium energies of 5 -10 eV. A more accurate calculation using a mixed physical and pseudostate basis was recently carried out [11] in the energy region below the ionization threshold. Besides is larger than the cross section from the positronium ground state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation